Characterization and Biogeographic Evaluation through the Lanbioeva Method of the Forests of Quercus Petraea of the Basque Country and Navarre (Iberian Peninsula) - Lozano-Valencia, Pedro José; Varela-Ona, Rakel; Lozano-Fernández, Asier; Meaza-Rodriguez, Guillermo (Revista de Estudios Andaluces, 2021)
The forests of Quercus petraea of the Basque Country and Navarre They are characterized and evaluate. Three are the locations chosen: south of Vizcaya, south of Guipuzcoa and north of Navarra. An inventory of 10 plots is undertaken for each location and different characteristics are analyzed: diversity, chorological affiliation, species status and application of the LANBIOEVA method. These oak forests are very scarce and have courtships where scarce plants also dominate. In these forests, dominate, in general, eurosiberian or Eurasian, Atlantic and transitional affiliations between the Mediterranean and the Atlantic. The oak forests of Navarra are configured as the most diverse, followed by Guipuzcoa and Vizcaya. Biogeographic evaluation results in high values for the three formations but higher in Pikandi and Garralda and more modest in Garrastatxu.